Granite-related uranium deposits in Argentina: Geological context and new metallogenetic studies. - Álvarez, J.; Parra, F.; Anzil, Patricia Andrea; Bello, C.; Ceballos, E.; Salvatore, M.; Scarlatta, L.; Miyno, S.; Felkai, E.; Ferreyra, P.; Zelaya, A.; Cuney, M.; et al. (Vienna International Centre. International Atomic Energy Agency, 2020)
Fil: Álvarez, J.. Comisión Nacional de Energía Atómica; Argentina